Interactions between tetracycline and extracellular polymeric substances in anammox granular sludge. (December 2019) - Liu, Song; Lin, Chong; Diao, Xingxing; Meng, Liao; Lu, Hui
Highlights: Tryptophan, tryptophan type-proteins and humic acids interacted with tetracycline. Tetracycline facilitated protein electronegativity and extension of peptide chains. Tetracycline decreased the extracellular polymeric substances resilience ability. The reaction of tetracycline and extracellular polymeric substances was hydrophobic. Abstract: The effects of antibiotics on extracellular polymeric substances (EPS) using tetracycline as the model chemical were analyzed in terms of molecular property and structure. Results showed that three components, tryptophan, tryptophan type-proteins and polysaccharides in EPS of granular sludge from anaerobic ammonium oxidation (anammox) reactor can interacted with tetracycline, detected by the static quenching via the endogenous fluorescence quenching and transient fluorescence spectroscopy. Thermodynamic experiment confirmed that their interaction was dominated by the hydrophobic force. Combined with the synchronous fluorescence spectroscopy, it was found that tetracycline facilitated the extension degree of peptide chains in tryptophan type-proteins, leading to the enhancement of hydrodynamic diameter of the macromolecules in EPS when binding with tetracycline. EPS in AnGS demonstrated the resistance ability to tetracycline by converting from gel to sol state in rheological term. With the increase of tetracycline concentration, the stability of elastic structures in EPS declined, influencing the AnGS stability.